EVALUASI SENSORIK DAN EFEKTIVITAS PRODUK SNACK BAR BERBASIS KACANG-KACANGAN UNTUK MENDUKUNG SIKLUS MENSTRUASI REGULER : - Putri Dewi; mastina (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2025)
Irregular menstrual cycles and premenstrual symptoms (PMS) are common issues among women of reproductive age, often linked to inadequate nutritional intake. Functional food products based on legumes are considered promising in supporting reproductive health. This study aimed to develop a legume-based snack bar and evaluate its effectiveness in improving menstrual cycle regularity. The research was conducted in two stages. The first stage involved the development of three snack bar formulas followed by sensory evaluation using a 5-point hedonic scale by 30 semi-trained panelists. The best-performing formula was analyzed for its nutritional content using proximate analysis and NutriSurvey software. The second stage was a quasi-experimental intervention involving 60 subjects randomly assigned to intervention and control groups. The intervention group consumed one snack bar (35 g/day) for four consecutive weeks. Menstrual cycle regularity and symptoms were assessed using a menstrual diary and the Modified Menstrual Symptom Questionnaire (M-MSQT). Formula 3 showed the highest sensory scores and contained 3.8 mg of iron per serving. Significant improvements were observed in menstrual cycle length, bleeding duration, dysmenorrhea intensity, and PMS scores in the intervention group (p < 0.05). The legume-based snack bar was effective in improving menstrual cycle regularity and reducing PMS symptoms, and may serve as a functional food innovation for young women.